High-Resolution Coproecology: Using Coprolites to Reconstruct the Habits and Habitats of New Zealand’s Extinct Upland Moa (Megalapteryx didinus) - Wood, Jamie R.; Wilmshurst, Janet M.; Wagstaff, Steven J.; Worthy, Trevor H.; Rawlence, Nicolas J.; Cooper, Alan (PLOS ONE, 2012)
Knowledge about the diet and ecology of extinct herbivores has important implications for understanding the evolution of plant defence structures, establishing the influences of herbivory on past plant community structure and composition, and identifying pollination and seed dispersal syndromes. The flightless ratite moa (Aves: Dinornithiformes) were New Zealand’s largest herbivores prior to their extinction soon after initial human settlement. Here we contribute to the knowledge of moa diet and ecology by reporting the results of a multidisciplinary study of 35 coprolites from a subalpine cave (Euphrates Cave) on the South Island of New Zealand. Ancient DNA analysis and radiocarbon dating revealed the coprolites were deposited by the extinct upland moa (Megalapteryx didinus), and span from at least 6,368±31 until 694±30 14C years BP; the approximate time of their extinction. Using pollen, plant macrofossil, and ancient DNA analyses, we identified at least 67 plant taxa from the coprolites, including the first evidence that moa fed on the nectar-rich flowers of New Zealand flax (Phormium) and tree fuchsia (Fuchsia excorticata). The plant assemblage from the coprolites reflects a highly-generalist feeding ecology for upland moa, including browsing and grazing across the full range of locally available habitats (spanning southern beech (Nothofagus) forest to tussock (Chionochloa) grassland). Intact seeds in the coprolites indicate that upland moa may have been important dispersal agents for several plant taxa. Plant taxa with putative anti-browse adaptations were also identified in the coprolites. Clusters of coprolites (based on pollen assemblages, moa haplotypes, and radiocarbon dates), probably reflect specimens deposited at the same time by individual birds, and reveal the necessity of suitably large sample sizes in coprolite studies to overcome potential biases in diet interpretation.